2011
DOI: 10.3343/kjlm.2011.31.4.265
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Determinants in Imipenem-nonsusceptible Acinetobacter calcoaceticus-baumannii Complex Isolated in Daejeon, Korea

Abstract: BackgroundMembers of the Acinetobacter calcoaceticus-baumannii (Acb) complex are important opportunistic bacterial pathogens and present significant therapeutic challenges in the treatment of nosocomial infections. In the present study, we investigated the integrons and various genes involved in resistance to carbapenems, aminoglycosides, and fluoroquinolones in 56 imipenem-nonsusceptible Acb complex isolates.MethodsThis study included 44 imipenem-nonsusceptible A. baumannii, 10 Acinetobacter genomic species 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 27 publications
4
18
0
Order By: Relevance
“…Our research revealed the co-occurrence of selected carbapenem and aminoglycoside resistance genes in 8 combinations, with the dominance of isolates carrying bla OXA-40-like , aac(3)-Ia and aph(3′)-VI genes (44.3%). The coexistence of genes accountable for resistance to carbapenems and aminoglycosides in isolates of A. baumannii was also found by Salazar de Vegas et al, Endimiani et al, Nigro et al, and Sung et al [18,2628]. A. baumannii multidrug resistance appears to be a consequence of accumulation of mutations and the acquisition of resistance determinants by the transfer of plasmids, transposons, and integrons, which may lead to the formation of clusters of resistance genes, termed “resistance islands” [6].…”
Section: Discussionsupporting
confidence: 57%
“…Our research revealed the co-occurrence of selected carbapenem and aminoglycoside resistance genes in 8 combinations, with the dominance of isolates carrying bla OXA-40-like , aac(3)-Ia and aph(3′)-VI genes (44.3%). The coexistence of genes accountable for resistance to carbapenems and aminoglycosides in isolates of A. baumannii was also found by Salazar de Vegas et al, Endimiani et al, Nigro et al, and Sung et al [18,2628]. A. baumannii multidrug resistance appears to be a consequence of accumulation of mutations and the acquisition of resistance determinants by the transfer of plasmids, transposons, and integrons, which may lead to the formation of clusters of resistance genes, termed “resistance islands” [6].…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies showed that class 1 integrons could be found in 44-84% of A. baumannii clinical isolates [15, 16]. Even in Acinetobacter complex isolates, integron-positive rates can go above 94% [17]. With 72% of the isolates studied in this study carrying integrons and integron-positive strains being more resistant to all of the tested antibiotics, we propose that the presence of integrons can be used as a representative marker of multidrug resistance in A. baumannii .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Doi et al (19) first discovered that two of five A. baumannii isolates coproduced OXA-23 β-lactamase and ArmA in North America in 2007. In addition, further cases were reported in Korea (20,23), India (24), France (25), Bulgaria (26), Italy (27), Latvia (28), East Africa (29), Yemen (30), Japan (31), Brunei (32), Egypt (33) and China (21,34,35). The authors of the present study previously determined that extended-spectrum β-lactamase and 16S rRNA methylase are coproduced in A. baumannii (36).…”
Section: Introductionmentioning
confidence: 99%